Environmental border tax adjustments and international trade law : fostering environmental protection - Pirlot, Alice (New horizons in environmental and energy law, 2017)
This timely book brings clarity to the debate on the new legal phenomenon of environmental border tax adjustments. It will help form a better understanding of the role and limits these taxes have on environmental policies in combating global environmental challenges, such as climate change. The book is structured around three main topics: the rationale, the tax design and the legal framework of environmental border tax adjustments. This three-fold analysis gives an overview of the legal issues that should be considered before the adoption of environmental border taxes, including carbon tax adjustments. Alice Pirlot's critical approach to the arguments surrounding traditional and environmental border tax adjustments allows for detailed legal analysis going beyond the question of their compatibility with WTO law, while also reviewing the economic argument. This book will prove to be essential reading for legal scholars and professionals alike, as well as benefitting environmental NGOs, stakeholders in energy-intensive industries and policymakers looking for in-depth insight into environmental border tax adjustments.